Air Parameter Analysis for Precision Agriculture in Controlled Engineering - Hajihil, Noorfarhanah (Journal of Advanced Industrial Technology and Application, 2022)
In a plant factory, an enclosed growing system, environmental parameters for the nutrients used are intentionally controlled, including temperature, carbon dioxide levels, humidity, light intensity, and humidity levels. The concept and objectives of this urban farming must be carried out under constant supervision, since this will affect the crop output. Unreliable patterns in variables have the drawback of ultimately causing the failure to achieve the objectives of the modern system. This study’s objective is to analyze the data pattern recorded by IoT system that is installed to determine the accuracy of the sensors and look at the trends in the variables that impact temperature, humidity, and gas concentration in precision agricultural facilities. Data analysis techniques were used to get the data for the instruments used in this investigation. According to the data that were examined, the variables of temperature, relative humidity, and gas concentration within the plant factory were unstable at times for the crops development. The next goal is to determine whether both LEPF and AgroX system’s sensor measure the selected parameter properly and able to provide reliable data for the variables.